The Influence of Work Motivation and Work Experience on Teacher Performance at Ukhuwah Integrated Islamic Elementary School Banjarmasin - Cristine, Marya Yully; Ritawaty, Noor; Pauziah,; Kadir, Abdul; Naimah, (Archives of Business Research, 2024)
The aim of this research is to determine the influence of work motivation and work experience on teacher performance at the Ukhuwah Integreted Islamic Elementary School, Banjarmasin. The technique used in this research is a quantitative method. This research was conducted on 70 respondents, who were teacher at the Ukhuwah Integreted Islamic Elementary School, Banjarmasin. The results of this research show that work motivation and work experience simultaneously and partially influence teacher performance at the Ukhuwah Integreted Islamic Elementary School, Banjarmasin. And the work experience variable has a dominant influence on teacher performance at the Ukhuwah Integreted Islamic Elementary School, Banjarmasin.